Yield evaluation of four cultivated banana (Musa acuminata) varieties and determination of the optimal plot size for statistical confidence of field assays in the Formosa province (Argentinean Northeastern) - Tenaglia, Gerardo Carlos; Keim, Cesar; Romero, Hernán; Pratta, Guillermo Raúl (Ediciones INTA, 2023)
Banana production on scientific basis is relatively new in Argentina. To evaluate potential productivity in the province of Formosa, four international banana varieties were tested over four campaigns at Estación Experimental Agropecuaria de INTA Chaco-Formosa. Data were also applied to determine the optimal plot size to confer statistical robustness to the field trials. Differences among varieties and among campaigns were detected but their interaction was not significant. Nevertheless, a biplot analysis identified patterns of differential performances and specific variety-campaign combinations. According to the maximum curvature method, plot size must include 6 to 8 plants of each variety for optimal statistical confidence of field trials. However, given that banana is a perennial crop and the Argentine environment is suboptimal for banana production, not all plants are productive every year. Hence, an optimum number of 10 plants is proposed to ensure statistical confidence in field trials in the province of Formosa.